Retirement motivation among ‘Malaysia My Second Home’ participants - Wong, K.M.; Musa, G. (Elsevier, 2014)
‘Malaysia My Second Home’ is an international retirement migration programme aimed at attracting the lucrative retiree market to choose Malaysia as their residence. This study implemented the concept of the Travel Career Ladder (TCL) (Pearce, 1991), with a purposeful sample of 30 participants who had retired to Malaysia. Questioning was directed towards their motives for selecting Malaysia and the analysis indicated that the majority of the motivation themes clustered in the seeking of self-fulfilment needs. Among motivation themes discovered are meaningful second life, positive instant thoughts, central travel location, positive retirement book description, food variety, tranquillity and simple life, political stability and security, and ease of communication. The study also revealed a challenge in applying TCL to its findings as some motivational themes simultaneously represent various TCL hierarchies. The theoretical, marketing and managerial implications of the study are discussed.